1990
DOI: 10.1246/bcsj.63.3640
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanism of Oxidation of Phosphinic, Phenylphosphinic, and Phosphonic Acids by Pyridinium Chlorochromate

Abstract: Oxidation of the lower oxyacids of phosphorus by pyridinium chlorochromate (PCC) results in the formation of the corresponding higher oxyacids of phosphorus. The reaction is of first order with respect to PCC and the oxyacid. The reaction is catalyzed by hydrogen ions, kobs=a+b[H+]. The reaction exhibited a substantial primary kinetic isotope effect. The rates in 19 different organic solvents have been analyzed using Kamlet–Taft’s and Swain’s equations. It has been found that the cation-solvating power of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Since protonation of alcohol is less probable it is more likely that both protons are used by the oxidant. Many workers have suggested protonated PCC [25][26][27] . The protonated PCC and alcohol combine to give intermediate, which was also indicated by decrease in rate with increase in dielectric constant of reaction medium due to more polar character of the transition state as compared to the reactants which is further attacked by proton.…”
Section: Discussionmentioning
confidence: 99%
“…Since protonation of alcohol is less probable it is more likely that both protons are used by the oxidant. Many workers have suggested protonated PCC [25][26][27] . The protonated PCC and alcohol combine to give intermediate, which was also indicated by decrease in rate with increase in dielectric constant of reaction medium due to more polar character of the transition state as compared to the reactants which is further attacked by proton.…”
Section: Discussionmentioning
confidence: 99%
“…In the chromic acid oxidation of PPA, however, Sharma and Mehrotra (1989) reported that it is not possible to pinpoint the reactive form of the reductant. In several recent studies on the oxidation of lower oxyacids reported from this laboratory, it was shown that the oxidations by pyridinium fluorochromate (Moondra et al 1990a), pyridinium chlorochromate (Seth et al 1990), N-bromoacetamide (Moondra et al 1991), ethyl Nchlorocarbamate (Asopa et al 1991), and bromamine-B (Moondra et ~l 1990b) do not involve the participation of the tricoordinated form. In view of the small equilibrium constant, the concentration of the tricoordinated tautomer in solution would be very small.…”
Section: Discussionmentioning
confidence: 99%
“…Under the present experimental conditions, the protonated chromium (VI) is presumed to be the reactive species since the rate increases with increase in [H + ]. The formation of a protonated species of PCC has been also reported [22][23][24] …”
Section: Effect Of Perchloric Acidmentioning
confidence: 99%